2017
DOI: 10.1007/s10900-017-0355-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Cervical Cancer Screening, Screening Behavior, and Post-Migration Living Difficulties Among Bhutanese–Nepali Refugee Women in the United States

Abstract: Bhutanese-Nepali refugees are one of the largest refugee groups to be resettled in the U.S. in the past decade. Cervical cancer is a leading cause of cancer disparity in this population, yet screening rates are suboptimal. Nepali-speaking interviewers administered a community health needs questionnaire to a convenience sample of Bhutanese-Nepali refugees in a Midwestern city between July to October of 2015. Descriptive statistics were used to describe socio-demographic characteristics, Pap smear beliefs, post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“… 57 Lower attendance was associated with a greater number of self-reported barriers to screening 61–65 although one study found the opposite. 66 However, the instruments used to assess barriers were largely based on existing instruments developed among Western samples that do not reflect South Asian concerns such as adapting to a new culture, language or health system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 57 Lower attendance was associated with a greater number of self-reported barriers to screening 61–65 although one study found the opposite. 66 However, the instruments used to assess barriers were largely based on existing instruments developed among Western samples that do not reflect South Asian concerns such as adapting to a new culture, language or health system.…”
Section: Resultsmentioning
confidence: 99%
“…Where acculturation was examined, less time spent in the host country was the strongest predictor of non-attendance, although one study cited lower preference for the host language (usually English) compared with women’s native language 65 and another self-perceived poorer command of the host language. 66 Vahabi et al 52 found that South Asian women were less likely to attend mammography screening if their general practitioner (GP) had qualified outside the host country. Lofters et al 77 also found that South Asian women were less likely to attend mammography screening if their GP had qualified outside the host country.…”
Section: Resultsmentioning
confidence: 99%
“…26 Although the suggestions for improving screening rates are useful, it is also important to consider the impact of cultural factors/barriers to screening that exist, particularly for cancers specific to women. 27 Studies have suggested that culturally competent outreach to particular immigrant communities is important, particularly in a country that welcomes many immigrants every year such as Canada. 28,29…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows the challenges of providing culturally and linguistically appropriate education to immigrant populations. [11][12][13][14] Despite the program removing most known barriers, screening uptake was lower in all populations compared to the U.S. national average and fell short of the Healthy People 2020 Targets of 93% for cervical, 81.1% for breast, and 70.5 for colorectal screening. [35] As of 2015, the screening proportions in the overall U.S. population were 81.2% for pap test, 71.6% for mammogram, and 62.4% for colon screening.…”
Section: Plos Onementioning
confidence: 99%